Penolong yang Sepadan menurut Kejadian 2:18 terkait Perdebatan Kepemimpinan Wanita dalam Gereja - Stella, Yunita (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The text of Genesis 2:18 is one of the passages debated by Complementarians and Egalitarians regarding the role of women as